Modeling patient-centered communication: Oncologist relational communication and patient communication involvement in breast cancer adjuvant therapy decision-making - Step, Mary M. (2009)
OBJECTIVE: Relational communication refers to those messages communicators naturally express that carry meaning about the type and quality of relationship they share. It is expected that patients of oncologists who express positive relational communication will be more communicatively involved in their office visits, and regret their decision for adjuvant therapy following surgery less. METHODS: One hundred eighty (180) audio-recorded discussions between oncologists (n = 40) and early stage (I–III) breast cancer patients were coded with the Siminoff Communication Content and Affect Program (SCCAP). The data were used to test the relationships between patient demographics, oncologist relational communication, patient communication involvement and self-reported patient decision regret. RESULTS: After controlling for clinician clusters, oncologists’ verbal (i.e., confirming messages) and nonverbal (i.e., direct and inclusive speech) relational communication is indirectly associated with lower patient decision regret via the mediating effect of greater patient communication involvement. CONCLUSION: Clinician relational communication provides an influential affective climate for decision-making that appears to have important effects on patients’ decision confidence. PRACTICE IMPLICATIONS: Clinicians should recognize the potential of their own relational messages to facilitate patients’ communication involvement in decision-making during cancer care.